Share Price Trend Prediction Using CRNN with LSTM Structure. Issue 3 (3rd July 2019) - Yu, Shyr-Shen; Chu, Shao-Wei; Chan, Yung-Kuan; Wang, Chuin-Mu
ABSTRACT: In this paper, the convolutional recurrent neural network (ConvLSTM) architecture is proposed to predict individual stock prices. The characteristics of stock data are automatically extracted through convolutional neural network (CNN). Afterward, the extracted features are inputted into a long short-term memory (LSTM) model with memory characteristics for prediction. Since CNN has been a representation learning model, it is quite appropriate for automatic feature extraction. Besides, the LSTM architecture of the recurrent neural network could effectively surmount the issues of gradient disappearance and expansion of the time series data. Ten stock historical data had been collected in the experimental data set. Furthermore, many commonly used technical indicators are calculated in advance for the expansion of the dimension of the training samples. The experimental results obtain a 3.449 RMSE (root-mean-square error) in average. Graphical Abstract The architecture of the ConvLSTM: